Bifunctional o-CoSe2/c-CoSe2/MoSe2 heterostructures for enhanced electrocatalytic and photoelectrochemical hydrogen evolution reaction. (March 2022) - Ji, Y.; Luo, W.; Liu, Y.; He, Z.; Cheng, N.; Zhang, Z.; Qi, X.; Zhong, J.; Ren, L.
Abstract: The bottleneck of alkaline hydrogen evolution reaction lies in the kinetically sluggish brought from multistep reaction processes involving water adsorption and dissociation, as well as hydrogen adsorption. In this work, we successfully synthesized o-CoSe2 /c-CoSe2 heterostructures anchored on MoSe2 nanosheets to powerfully promote reaction processes. As an electrocatalyst, it exhibits a low overpotential of 112 mV at 10 mA/cm 2 and a Tafel slope of 96.9 mV/dec for an alkaline hydrogen evolution reaction. Moreover, the as-prepared catalyst can behave as both cathode and anode for overall water splitting, which only requires 1.61 V cell voltage at 10 mA/cm 2 . Significantly, the cell voltage can be further reduced to 1.53 V at 10 mA/cm 2 for water electrolysis under the simulated solar irradiation owing to such a semiconductor-based heterostructure that facilitates the separation of photogenerated charges. Here, the improving overall performance of this ternary electrocatalyst is attributed to the multifunctionality and synergistic interaction of different components in this heterogeneous material. The work provides a novel strategy to design active catalysts simultaneously using electric energy and solar energy for effective water splitting. Graphical abstract: Image 1 Highlights: Ternary o-CoSe2 /c-CoSe2 /MoSe2 multisite heterostructures supported on carbon cloth are prepared. This ternary heterostructure behave as an effective bifunctional catalyst for both HER and OER. The cell voltage toward water splitting can be further reduced by involving solar energy. The multiple functional sites of these heterostructures contribute the good performance.